Temporal Trend and Health Inequality in the Burden of Autoimmune Diseases Among Older Adolescents and Young Adults Aged 15-29 Years - Li, Sheng; hu, Yan-yu Z; Musonye, Harry Asena; Shi, Qian-qian; Wei, Hai-fen; Zhao, Shu-shan; Pan, Hai-feng; Wang, Peng (Archives of Rheumatology, 2025)
Background/Aims: Autoimmune diseases (ADs) are a group of disorders characterized by the dysfunction of the immune system, leading to selfdirected attacks on organs or tissues. The global burden of ADs in older adolescents and young adults is still lacking and requires updates.This study described the global, regional, and country-specific disease burden and temporal trends of ADs in older adolescents and young adults (aged 15-29 years) from 1990 to 2019. Materials and Methods: Data from the 2019 Global Burden of Disease, Injury, and Risk Factors study were utilized to report age-standardized incidence rate (ASIR), age-standardized prevalence rate (ASPR), age-standardized mortality rate (ASMR), and age-standardized disability-adjusted life years (ASDR) rates of ADs at global, regional, and national levels. The average annual percent change was determined by Joinpoint regression analysis. Results: In 2019, the burden of alopecia areata (AA) and rheumatic heart disease (RHD) in older adolescents and young adults was particularly notable. Specifically, the ASIR for AA was 493.84 per 100 000 (95% uncertainty interval (UI): 444.13, 544.49), while the ASPR, ASMR, and ASDR for RHD were 771.43 per 100 000 (95% UI: 529.38, 1074.04), 1.08 per 100 000 (95% UI: 0.94, 1.23), and 108.36 per 100 000 (95% UI: 88.63, 133.67), respectively. From 1990 to 2019, the heavy disease burden of ADs was more pronounced in the European region and region of the Americas, where Italy and El Salvador were particularly affected. Although the burden of ADs was generally more severe in females than in males across most regions, males consistently had higher ASIR (10.19 per 100 000; 95% UI: 4.68, 18.22), ASPR (249.77 per 100 000; 95% UI: 186.89, 325.98), ASMR (0.53 per 100 000; 95% UI: 0.47, 0.60), and ASDR (47.59 per 100 000; 95% UI: 40.97, 56.34) for type 1 diabetes mellitus (T1DM) compared to females. Conclusion: Globally, there is an increasing burden of AA, T1DM, and RHD in older adolescents and young adults. The American and European regions and females endure a severe burden of ADs. Healthcare providers should be aware of the heavy burden of ADs and develop age-appropriate prevention, diagnosis, and intervention strategies to achieve health equity.